2009
DOI: 10.1177/0146167209351886
|View full text |Cite
|
Sign up to set email alerts
|

Same or Different? Clarifying the Relationship of Need for Cognition to Personality and Intelligence

Abstract: Need for cognition (NFC) refers to an individual’s tendency to engage in and enjoy effortful cognitive processing. So far, little attention has been paid to a systematic evaluation of the distinctiveness of NFC from traits with similar conceptualization and from intelligence. The present research contributes to filling this gap by examining the relation of NFC to well-established personality concepts (Study 1) and to a comprehensive measure of intelligence in a sample with broad educational backgrounds (Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

23
220
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(247 citation statements)
references
References 47 publications
23
220
1
3
Order By: Relevance
“…Based on these studies we expected high temporal stability (i.e., test-retest reliability) of the METQ. In contrast to temporal stability, the internal stability of NFC has been frequently examined, with most studies showing high internal stability that is above 0.80 [see, e.g., Venkatraman and Price (1990), Cacioppo et al (1996), Fleischhauer et al (2010), and Preckel (2014)]. A similar result is expected in the present study.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Based on these studies we expected high temporal stability (i.e., test-retest reliability) of the METQ. In contrast to temporal stability, the internal stability of NFC has been frequently examined, with most studies showing high internal stability that is above 0.80 [see, e.g., Venkatraman and Price (1990), Cacioppo et al (1996), Fleischhauer et al (2010), and Preckel (2014)]. A similar result is expected in the present study.…”
supporting
confidence: 86%
“…The significance of NFC as a moderator of information processing was also shown in a study of information search and interactive web pages (Sicilia et al, 2005). Cacioppo and Petty (1982) developed a scale to measure NFC, which has been explored in relation to a variety of individual differences, such as intelligence, personality, and academic achievement [see, e.g., Cacioppo et al (1996), Fleischhauer et al (2010), and Preckel (2014)]. The original and short version of the NFC-scale is, according to Cacioppo et al (1996), reasonable, reliable, and valid.…”
mentioning
confidence: 99%
“…Even on the meta-analytic level, evidence is mixed regarding the effectiveness of cognitive training in both younger and older adults (e.g., Au et al 2015;Dougherty et al 2016;Karbach and Verhaeghen 2014;Kelly et al 2014;Lampit et al 2014;Melby-Lervåg and Hulme 2013;Melby-Lervåg et al 2016;Schwaighofer et al 2015;Soveri et al 2017). Aside from design and methodological choices potentially explaining the diverging findings (e.g., Noack et al 2009;Shipstead et al 2012), many authors increasingly articulated the potentially important influence of individual differences on cognitive training trajectories and outcomes (e.g., Buitenweg et al 2012;Guye et al 2016;Könen and Karbach 2015;Shah et al 2012;von Bastian and Oberauer 2014 Individual differences in cognitive functioning (e.g., Ackerman and Lohman 2006) and learning potential (e.g., Stern 2017) accentuate with increasing age (e.g., Rabbitt et al 2004) and have been shown to be related to personality (e.g., Graham and Lachman 2012), cognition-related beliefs such as need for cognition (NFC; e.g., Fleischhauer et al 2010;Hill et al 2013), and everyday life activities (e.g., Jopp and Hertzog 2007). Investigating which of these individual differences potentially predict cognitive training outcomes may not only explain inconsistencies concerning the effectiveness of cognitive training, but also identify possible subgroups of individuals that are more or less responsive to cognitive training, thereby constituting the conceptual groundwork for developing individually tailored interventions to boost training effectiveness.…”
mentioning
confidence: 99%
“…Individual differences in cognitive functioning (e.g., Ackerman and Lohman 2006) and learning potential (e.g., Stern 2017) accentuate with increasing age (e.g., Rabbitt et al 2004) and have been shown to be related to personality (e.g., Graham and Lachman 2012), cognition-related beliefs such as need for cognition (NFC; e.g., Fleischhauer et al 2010;Hill et al 2013), and everyday life activities (e.g., Jopp and Hertzog 2007). Investigating which of these individual differences potentially predict cognitive training outcomes may not only explain inconsistencies concerning the effectiveness of cognitive training, but also identify possible subgroups of individuals that are more or less responsive to cognitive training, thereby constituting the conceptual groundwork for developing individually tailored interventions to boost training effectiveness.…”
mentioning
confidence: 99%
“…Our primary outcome measures involved a series of cognitive abilities tests measuring constructs that have been previously demonstrated to be involved with activities related to the Need for Cognition [22][23][24]: (1) Similarities -participants describe how similar two words or concepts are, measuring verbal concept formation and reasoning; (2) Number series -respondent looks at a number series with a missing number, determining the pattern and identifies the missing number to complete a numerical sequence. It measures quantitative reasoning; (3) Picture vocabulary -respondents identify familiar and unfamiliar pictured objects, measuring aspects of lexical knowledge; (4) Auditory working memory -respondent listens to mixed series of words and digits while attempting to reorder them by words and numbers in order.…”
Section: Variablesmentioning
confidence: 99%